A Perturbation Method for the Numerical Solution of the Bernoulli Problem (Journal of Computational Mathematics, 2018)
We consider the numerical solution of the free boundary Bernoulli problem by employing level set formulations. Using a perturbation technique, we derive a second order method that leads to a fast iteration solver. The iteration procedure is adapted in order to work in the case of topology changes. Various numerical experiments confirm the efficiency of the derived numerical method.